Pengaruh Manajemen Laba (Eamings Management) Terhadap Kinerja Operasi dan Return Saham di Sekitar IPO: Studi terhadap Perusahaan yang Listing di Bursa Efek Jakarta - Yustisia, Anelies; Andayani, Wuryan (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2006)
The purposes of this study are to know and to get empirical proof whether the company have earning management in IPO, how the performance of company operation and stock return of company a year after IPO. Beside, it is also regarded to know how is the effect of earning management toward operation performance of company and the effect of earning management toward stock return. The data is needed in this study is the prospect financial report and company financial report two years after IPO. This study uses company data that have IPO in 1993 up to 2001, so that the data period of company that is obtain include the data from 1991 up to 2003. Earning management measurement is based on discretionary accrual (DA) value. The operation performance is measured by using return on asset (aROA) alteration. The examination toward the effect of earning management toward stock return begin by examining whether stock return after IPO is low by using cumulative abnormal return (CAR). Each of the result of examination will be reexamined by using parametric statistical examination that is one sample t-test by Ã = 5%. The results of this study shows the indication of earning management in the period before and after IPO. This study is fail to show that there is any significant decrement of company operation performance, and cannot prove that it is occurred because of earning management. This study success to show the decrement of stock performance after IPO. Beside, it can be shown that the stock performance decrement is caused by earning management that is conducted in IPO. Keywords: earning management, IPO, operation performance, stock return